Financial Supply Chain Management, Operational Efficiency and Capital Assets: A new Insight from Kuwait - Ahmed Nahar Al Hussaini (International Journal of Supply Chain Management, 2019)
Although numerous studies have provided their theoretical and empirical contribution for supply chain, but the context of financial trends in SC are missing. This study aims to considers the factors under the title of financial supply chain and their association with the operational efficiency, capital assets of the business. To address this objective, a sample of 140 manufacturing firms, working in the region of Kuwait has been finalized over 9 years (2007-15). For operational efficiency, five measures have been considered. While capital assets are considered through fixed and financial dimensions of investment as appeared in the balance sheet. Data is collected from the online sources, reports and financial statements of selected companies. Both descriptive and regression findings are presented to empirically examine the relationship between financial dimension of supply chain, operational efficiency and capital assets. It is found that operational factors like OPM, GPM and NPM are significant associated with CL, NWC, cash, inventory and creditors account. While, investment in fixed assets has its significant and positive association with all the dimensions of financial supply chain management. Meanwhile, financial assets are assumed to the significant determinants of 2nd three indicators of supply chain. As per the findings, this study contributes in the literature in both theoretical and practical perspective. Core limitations include non-consideration of cost-based efficiency measures, ignoring financial and economic sustainability and non-application of modern analysis techniques.